(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Rice (Oryza sativa L.) is a staple food which contains a high amount of nutrients essential for human nutrition, energy supply, and food security. Despite its nutritional value, it does not reach its physiological maturity at the same time thereby affecting the quality of seeds produced when harvested. The overarching objective of this research was to determine the influence of harvesting days on seed yield and quality of two rice varieties (Jasmine 85 and Amankwatia) at the Department of Horticulture, Kwame Nkrumah University of Science and Technology, Ghana. A 2 x 3 factorial arranged in a Randomized Complete Block Design with three replications was the study design. Factor one was the two varieties (Jasmine and Amankwatia) and factors two was different harvesting times at three levels [105, 112 and 126 days after transplanting (DAT)]. The study revealed that Jasmine 85 had the highest plant height, number of panicles and number of tillers. The study also showed that the interaction of the varieties and different harvesting times had a significant influence on the germination percentage, germination energy, germination rate index and mean germination time. The study showed that Amankwatia harvested at 126 DAT and Jasmine harvested at 112 DAT respectively, performed the best in terms of yield. Furthermore, Amankwatia harvested at 112 DAT and Jasmine harvested at 105 DAT respectively, also improved germination parameters. Harvesting of both varieties (Jasmine and Amankwatia) at 112 DAT and 126 DAT will maximize yield, while harvesting at Amankwatia at 112 DAT and Jasmine at 105 will improve germination. Int. J. Agril. Res. Innov. Tech. 14(2): 122-131, December 2024